Two-phase spray cooling for high ambient temperature data centers: evaluation of system performance - Kandasamy, Ranjith (2022)
A lab-scale spray cooled rack system with a server and simulated heaters, operating with near-ambient temperature coolant of approximately 30 °C, was developed for data center cooling application. This system has significant energy saving potential as it eliminates the need for a chiller unit, which is usually necessary in conventional air-cooling schemes. The system was designed to dissipate a maximum heat load of 5.6 kW. Despite its higher operating temperature, our investigation shows that the spray cooled system leads to better cooling performance of the microprocessors as compared to conventional air-cooling scheme. A durability study for more than 40 h of cumulative intermittent operation showed no degradation in system performance when operated at high chamber temperature conditions (>35 ℃). The thermal performance of the spray cooled system and the effects of parameters such as spray nozzle flow rate, condenser fan power, condenser flow rate and heat loads were systematically characterized. It is found that the thermal performance of the simulated heaters is mainly affected by the spray nozzle flow rate, while the condenser fan power and condenser cooling water flow rate strongly affect the condensation rate and are, therefore, critical parameters for spray chamber pressure control. In summary, this work demonstrates the possibility of employing the newly developed spray cooled system for the thermal management of high-performance servers of data centers in tropical climates and identified key operating parameters that are useful for the design, operation and implementation of this system.